Contágio no modelo de Allen e Gale com infraestrutura bancária endógena - Silva, Diego Martins (2015)
In this work, we analyze network formation with wary agents. The model consists of two regions with (n/2) banks in each, where the connection between them occurs through interbank deposits. A bank run is possible to occur in each bank, due to an increase not expected of impatient agents, or due to contagion from run in another bank. If all banks form a high number of interconnections, they can eliminate possibility of contagion. If one does not prevent a contagion, it imposes all the others banks a positive possibility in the worst case. There are two well-deﬁned regions of symmetric nash equilibrium with stable network, one in which all banks prevents the contagion in the worst case and the other in which no bank prevents. As a result of the coordination problem, equilibrium with contagion in the worst case can occur even pareto dominated by the equilibrium without contagion. Under certain conditions, contagion in the worst case occurs with a network pareto efﬁcient, nevertheless the network is not the most resilient one.